Preliminary study of the antimicrobial activity of guava (psidium guajava) extract as soap additive. - Castro, Judith Simoy
The study evaluated the efficacy of Psidium guajava (guava) leaf extract as additive for antimicrobial soaps. Results fort he bioassay of crude ethanolic "Guava" extracts showed that crude extract indeed exhibited antimicrobial activity against B. subtilis, E. coli, P. aeruginosa ans S. aureus, which confirmed the former studies. Results on the phytochemical field test indicate the absence of alkaloids but flavonoids and saponins are present int he amples. Results on cytotoxicity test show that "Guava" extracts are non-toxic and safe to use as an additive in soap mixtures since the lethal dose concentration at 50 percent mortality (LC50) is 1,362 ppm., Five types of soaps were prepared by mixing different kinds, combinations and proportions of fats and oils (coconut oil, corn oil, olive oil, soybena oil, and tallow) with different amounts of extract (0.2 percent, 0.5 percent an 08 percent). Results for the Determination of the Saponification Number of fats and oils were used to determine the amount of base needed in the soap making process. After four weeks of aging, most "Guava" soaps have pH 11. A slight drop in pH, from pH 11 to pH 10, was observed after another four weeks. The color of "Guava" soaps, which is generally brown due to the color of the extract, intensity as the concentration of the extract was increased but this color lightens as the soap aged. Almost all of the soap product have hard and smooth texture, produces fine bubbles and have moisturizing effect on the skin with no itchiness felt. Results of the antimicrobial assay by Paper Disc Diffusion Method showed that all "Guava soaps have antimicrobial property. The antimicrobial activity of the soaps increases as the concentration of the extract was increased. Generally, the antimicrobial indexes of the different soap types with different concentration of "Guava" extract were found to be significantly different. Soaps with 0.8 percent "Guava" extract, which exhibit the highest antimicrobial activity, were then tested for its degerming activity on the skin. Results showed significant difference among the number of bacterial colonies formed by different soap types. Efficacy of "Guava" soaps as skin degerming agent was comparable to the commercial soaps as shown by duncan Multiple Range Test. Among the five types of soaps prepared Soap V which contains the mixture of coconut oil, soybean oil and tallow in a ratio of 1.75:3.25:1 is considered to be the best based on the physical characteristics, affordability and availability of the raw materials as well as, its antimicrobial property.